Molecular identification of the CRAC channel - Cahalan, Michael (Henry Stewart Talks, 2007)
Background on Calcium signaling and ion channels in the immune system, role of CRAC channels in lymphocyte activation, Discovery of Stim and STIM1 by RNA interference screen in Drosophila S2 cells, Stim as an ER Calcium sensor and as a messenger to the plasma membrane, Genome-wide RNA interference screen and the discovery of Orai, Amplifying CRAC current by co-expression of Stim and Orai, Molecular identification of CRAC channels by altered ion selectivity in a mutant of Orai, How does the CRAC channel activate?